Fertilização nitrogenada à dose variada na cultura do milho - Bragagnolo, Jardes (2014)
Maize is the main cereal produced in Brazil, being highly responsive to nitrogen fertilization, since the tropical and subtropical soils presents insufficient availability of nitrogen (N) to attend the culture demand in order to obtain high yields. Adjustments in the rate of N fertilizer can be made during the development of the culture through of the use of optical sensors spectrometry. The aim of this study was to evaluate the efficiency of nitrogen fertilization to the variable rate prescribed by use of the N -Sensor® ALS, and correlate it with different plant attributes during development of maize in RS Oxisols. Three experiments were conducted, two in the 2008/09 and another in the 2010/11 season. The ability of the sensor to determine the nutritional status of the culture and the effect of different rates of N, uniform and variable rate, on the following attributes of the plant were evaluated: N content of the plant tissue, the total N uptake by the crop, dry matter and relative chlorophyll content measured by chlorophyll meter readings with manual and on grain yield and N use efficiency. The plant attributes and corn yield were largely influenced by nitrogen fertilization and the intrinsic climatic conditions of each experiment. During fertilization optical sensor was able to assess on average 34 % of the plants in the experimental areas, which obtained high ratio of the readings of the optical sensor with the amount of N uptake and dry matter of corn plants, despite loss efficiency (saturation) observed in the later stages of crop development. Whereas maize absorbed most of the N after the V8 stage of development, the use of the optical sensor grown in the same or in later stages of development is a viable strategy for the nitrogen source at varied doses. Nitrogen fertilization at variable rate based on optical sensor promoted an increase of N uptake by 11.8 % in relation to nitrogen fertilization uniform rate in the third experiment. In all areas investigated, grain yield increased in response to nitrogen fertilization, getting above national average productivities. The use of fertilizer N rate variable strategy despite the slight increase in grain yield of maize was not able to make a statistically significant increase. The efficiency of use of N different indexes evaluated showed improvement with the use of N variable rate based on the optical sensor to the uniform rate. The strategy of N variable rate proved to be efficient as the use of N as measured by a decrease and increase of N rate prescribed by the optical sensor as the nutritional status of the crop, with an effective strategy of the environmental point of view, by reduced risks associated with nitrogen over fertilization.